1980
DOI: 10.1108/eum0000000004899
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Use of Power

Abstract: Focuses on ways in which channel co‐operation and co‐ordination can be improved and unnecessary dysfunctional conflict reduced. Maintains that the purpose herein is to provide a better understanding of power relationships in marketing channels so that the likelihood of positive outcomes is increased, as this insight is important for both the systems and independent perspectives. Purports that power is the vehicle by which the range of variability in channel behaviour is limited, and a measure of predictability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 7 publications
4
47
0
Order By: Relevance
“…Similar argument can also be found in the literature (Leet-Pellegrini & Rubin, 1974;Brown, Lusch & Nicholson, 1995). Therein, Kasulis and Spekman (1980) pointed out the use of reward, coercion, and legitimate oriented incentives which appear to have positive effects on the target members' compliance (even though short-term sacrifice is needed); in contrast, the use of both reference and expertise oriented incentives can lead to the target member's sense of identification with the source member thus enhancing its confidence in the stability of the relationship. Lawler and Yoon (1993) further argued that relative to coercion, the use of noncoercive power source can be more helpful to improve the satisfaction of the dyadic member in the partnership leading to more confidence in the stability of channel relationship.…”
Section: Use Of Various Independent Incentives and Relationship Commimentioning
confidence: 65%
“…Similar argument can also be found in the literature (Leet-Pellegrini & Rubin, 1974;Brown, Lusch & Nicholson, 1995). Therein, Kasulis and Spekman (1980) pointed out the use of reward, coercion, and legitimate oriented incentives which appear to have positive effects on the target members' compliance (even though short-term sacrifice is needed); in contrast, the use of both reference and expertise oriented incentives can lead to the target member's sense of identification with the source member thus enhancing its confidence in the stability of the relationship. Lawler and Yoon (1993) further argued that relative to coercion, the use of noncoercive power source can be more helpful to improve the satisfaction of the dyadic member in the partnership leading to more confidence in the stability of channel relationship.…”
Section: Use Of Various Independent Incentives and Relationship Commimentioning
confidence: 65%
“…Identification has been recognized as a key source of influence and power in marketing channels (Kasulis and Spekman 1980;Lusch and Brown 1982), but the research reported in this study suggests it can also serve to inoculate and protect a firm's relational resources when a firm may do things that may not be in the best interests of its channel partners. Some of the tactics or programs that might foster identification include cobranding with business partners, collaborative planning and forecasting, helping business …”
Section: Managerial Implicationsmentioning
confidence: 92%
“…The "noneconomic" bases, namely referent, expert, and legitimate bases, are widely found to have a weak or insignificant relationship to the channel leader's influence (J. R. Brown et al, 1983;Keith, Jackson, & Crosby, 1990). Measurement of the effects of noneconomic bases is arguably problematic, because their use promotes identification or internalization, and hence the appearance of control is masked (Kasulis & Spekman, 1980). Interrelationships in power-base effects also complicate this area of research (Gaski, 1986).…”
mentioning
confidence: 96%
“…The dominance of the theme derives from its clear importance to managers. From the systems perspective (Kasulis & Spekman, 1980), influence over marketing decisions throughout the channel is critical to sustained advantage (Bucklin, 1973;El Ansary & Stern, 1972). It is then of practical interest to know who influences decisions in an interorganizational marketing channel and how one member can increase his or her influence.…”
mentioning
confidence: 99%